H-SPREAD: hybrid multiground chart for safe and reliable capture of data in wireless sensory networks - Дворская, Л. А. (Problems of Informatization and Control, 2007)
The hybrid multipass chart (H-SPREAD) of collection and passing to information is offered, allowing to promote reliability and protected of exchange information in a wireless sensory network. A chart is based on distributed N-to-1 the multigrain protocol of discovery, allowing during one process of discovery way of connection of every sensor simultaneously to define a few ways. Through multipass dispersal of information, combined with the division of secret, multiplies safety of through delivery information, and the changing of routing of ways, accessible on every sensor, multiplies reliability of every batch communication of data considerably